2021
DOI: 10.1016/j.sjbs.2021.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and risk factors of sharp object injuries among health care workers in two tertiary hospitals, Al Taif-Kingdom of Saudi Arabia 2016–2018

Abstract: Occupational exposure of healthcare workers to blood and body fluids following skin injury constitutes a risk for transmission of blood-borne pathogens. The risk of exposure is greater as well. The present study aimed to determine the burden and risk factors of sharp object injuries in two tertiary hospitals in the Taif City KSA. Retrospective review of needle stick injury records was included from the two hospital's staff clinics. A Total of 131 health professionals (employees) recorded as exposed to sharp ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…The exposure of nurses and midwives to cuts, wounds, needle pricks, and injuries from sharps is not surprising due to their frequent use of sharp objects, such as needles, for injections and other sharp objects at the workplace [ 25 ]. This finding is comparable to a study in Saudi Arabia that reported that among healthcare workers, nurses (56.5%) were the most affected by sharp object injuries at the workplace [ 26 ]. A higher prevalence of needle stick injuries has also been reported among Iranian nurses in the workplace [ 27 ].…”
Section: Discussionsupporting
confidence: 84%
“…The exposure of nurses and midwives to cuts, wounds, needle pricks, and injuries from sharps is not surprising due to their frequent use of sharp objects, such as needles, for injections and other sharp objects at the workplace [ 25 ]. This finding is comparable to a study in Saudi Arabia that reported that among healthcare workers, nurses (56.5%) were the most affected by sharp object injuries at the workplace [ 26 ]. A higher prevalence of needle stick injuries has also been reported among Iranian nurses in the workplace [ 27 ].…”
Section: Discussionsupporting
confidence: 84%
“…A study conducted in Felege Hiwot Referral Hospital indicated that health care workers working in the maternity unit were 99.1% less likely to sustain needle stick injuries than those working in the laboratory unit [12]. Another study conducted by [13] indicated that the medical department/medicine department recorded a high incidence of injuries with 51.9 %.…”
Section: Discussionmentioning
confidence: 99%
“…8 Cut wounds (17.6%) and needle prick (79.4%) are the most common type of injuries. 12 Factors found to influence contact to sharp objects are the workplace environment, distress, work types and load. 8 In the same study, Filipinos (32.1%) had the highest exposure to sharp objects, followed by Saudi (23.7%) and Indians (19.8%) in Taif City, Kingdom of Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%